ДОМОГОСПОДАРСТВА НА ФІНАНСОВОМУ РИНКУ УКРАЇНИ: ПОВЕДІНКОВО-МОТИВАЦІЙНИЙ АСПЕКТ - Кізима, Тетяна Олексіївна; Кізима, Андрій Ярославович (Науковий журнал «Світ фінансів», 2017)
Кізима Т. О., Кізима А. Я. Домогосподарства на фінансовому ринку України: поведінково-мотиваційний аспект. Розглянуто теоретико-інституційні та мотиваційні основи ощадно-інвестиційної поведінки домогосподарств на фінансовому ринку. Проаналізовано основні форми заощаджень домогосподарств (банківські депозити, вклади у небанківських фінансово-кредитних установах, цінні папери, золото) упродовж 2010–2015 рр. Наголошено на ключових проблемах, пов’язаних із функціонуванням пріоритетних для населення сегментів фінансового ринку України. Окреслено зарубіжний досвід діяльності домогосподарств на фінансових ринках провідних країн світу. Надано рекомендації щодо активізації ощадно-інвестиційної поведінки домогосподарств у сучасних умовах. Кизыма Т. А., Кизыма А. Я. Домохозяйства на финансовом рынке Украины: поведенческо-мотивационный аспект. Рассмотрены теоретико-институциональные и мотивационные основы сберегательно-инвестиционного поведения домохозяйств на финансовом рынке. Проанализированы основные формы сбережений домохозяйств (банковские депозиты, вклады в небанковских финансово-кредитных учреждениях, ценные бумаги, золото) в течение 2010–2015 годов. Отмечены ключевые проблемы, связанные с функционированием при- оритетных для населения сегментов финансового рынка Украины. Дана характеристика зарубежного опыта деятельности домохозяйств на финансовых рынках ведущих стран мира. Даны рекомендации по активизации сберегательно-инвестиционного поведения домохозяйств в современных условиях. Kizyma T., Kizyma A. Households in the financial market of Ukraine: behavioral-motivational aspect. Introduction. Savings are an important part of the household finance operation and management which not only contribute to meeting the future needs of households, but also affect the development of the national economy in general. However, in order for the savings of the population to be effectively used by other economic entities, they must first be properly organized and then transformed into investments through a variety of instruments traded on the financial market.Purpose of the research is to investigate the behavioral and motivational dominants in the saving and investment activity of domestic households on the financial market of Ukraine and make recommendations for its revitalization in modern conditions.Results. Considering this study we affirm the low level of savings and investment activity of households in Ukraine, their irrational financial behavior, a significant impact on the financial decisions of macroeconomic factors. In general, we must note a low domestic tendency of households to save, which has a negative impact on savings’ investment potential, efficiency and expediency of consumer spending. A number of reasons are the cause for such situation, including low levels of financial market infrastructure in general and in particular financial intermediation; low level of trust in the financial and credit institutions; continued socio-economic and political instability; low level of financial literacy; lack of governmental incentives for the saving and investment behavior of households.Conclusion. The most crucial priorities of the state policy are to stimulate savings and investment behavior of the population, which in our view should be the following: raising the level of financial literacy and promotion of savings and investment ideology and culture among domestic households, increasing the reliability of the protection of organized savings, development of financial intermediation and diversification of financial instruments for the use by ordinary citizens.